THE EFFECT OF TEACHERS’ WRITING APPROACH ON STUDENTS’ WRITING ACHIEVEMENT - Lazaar, Lamyae (PUPIL: International Journal of Teaching, Education and Learning, 2019)
The main purpose of this study is to explore the different approaches teachers adopt to teach writing skills at university. This study aims also at finding the effect of the writing approaches used by university teachers on students’ writing achievement. To meet these objectives, two research instruments were used, and four teachers and 158 students participated in this study. The findings reveal that teachers base their courses on three approaches; Genre Approach, Product Approach, and Process Approach. Teachers use Genre Approach to introduce the text structure in the writing course and then opt for either Product Approach or Process Approach to involve students in writing. The results indicate also that the approaches used by teachers do not affect students’ writing achievement. More research should be carried out in order to know the reason behind using only three approaches. Indeed, this issue is rarely investigated mainly at the University although writing skill is considered as the backbone of the English department. Ultimately, a number of pedagogical implications were drawn from this research, which are geared toward encouraging teachers to adopt more recent approaches to teaching writing that seek to involve the learner in the process of writing.